Sebaran Ukuran Rajungan Hasil Tangkapan Gillnet dengan Jarak Lokasi Penangkapan Berbeda di Perairan Kabupaten Pangkep - Ihsan Ihsan; Mustamin Tajuddin; Hasrun Abdullah; Zainuddin Zainuddin (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2021)
The aim of this study was to study the frequency distribution of the size and number of gillnet catches at different fishing locations. The data needed are primary and secondary data. Materials and tools used are long rulers, cameras, and crabs. The data were analyzed using frequency distribution analysis of the size of the crab catches. The structure of the frequency distribution of size (cm) of crab production with a gillnet to different fishing locations in the waters of Balang Lompo Island, Pangkep Regency, shows that there are differences, generally the smallest size is 0-2 miles, and distances are >2-4 miles and distances >4- 6 miles, crab production is getting bigger. Significant differences in terms of differences in the size of the crab production, are smaller near the coast and more numerous than offshore. The further distance from the beach for crab production, the size distribution of crab production is large and there are many in the waters closer to Balang Lompo Island, Pangkep Regency.